The effect of social comparison on debt taking: Experimental evidence - Antonia Grohmann; Melanie Koch (Deutsches Institut für Wirtschaftsforschung (DIW), 2022)
A number of studies show that there is a link between social comparison and high levels of household debt. However, the exact mechanisms behind this link are not yet well understood. In this paper, we disentangle two mechanisms by performing a lab experiment designed to study the effects of social image concerns and peer information on consumption choices financed through debt taking. We find that having to announce one's consumption decision publicly makes participants less likely to take debt and more likely to leave money on the table. The more information participants receive about other participants' choices, the more they seem to conform to these choices, leading to slightly increased debt taking and leaving money on the table.
Keywords: D14; G51; D91; 330; Household Finance; Lab experiment; Social Comparison; Peer Effects